2016
DOI: 10.1590/1982-43272664201611
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Behavior of Children in a Daycare Center

Abstract: Abstract:The present work examined aggressive behavior in a sample of children attending a child daycare center in relation to their teachers' behaviors and the types of activities proposed by them. Four teachers and their respective students were observed for an average of six sessions, during which they performed activities, which could be free (without instruction) or guided. The most frequent behaviors were pushing/pulling, fighting over objects/taking an object from someone else, and kicking/throwing obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, previous studies found discrepant results in this regard because children who attended daycare are generally considered more socially competent, but it is not so clear whether they are also more prosocial than those who did not attend it ( Erel et al, 2000 ; Belsky et al, 2007 ; Ansari, 2018 ; Bleiker et al, 2019 ). At the same time, daycare attendees may also be more involved in and exposed to aggressive behaviors among peers, as children exhibit their peak of physical aggression generally between 18 and 30 months of age ( Huston et al, 2015 ; Pingault et al, 2015 ; Filho et al, 2016 ; Ansari, 2018 ). Observing other children’s aggressive behavior has a noticeable effect, as children tend to imitate it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies found discrepant results in this regard because children who attended daycare are generally considered more socially competent, but it is not so clear whether they are also more prosocial than those who did not attend it ( Erel et al, 2000 ; Belsky et al, 2007 ; Ansari, 2018 ; Bleiker et al, 2019 ). At the same time, daycare attendees may also be more involved in and exposed to aggressive behaviors among peers, as children exhibit their peak of physical aggression generally between 18 and 30 months of age ( Huston et al, 2015 ; Pingault et al, 2015 ; Filho et al, 2016 ; Ansari, 2018 ). Observing other children’s aggressive behavior has a noticeable effect, as children tend to imitate it.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is unclear how long these effects of daycare may influence subsequent behavior, i.e., whether the experience of daycare can be considered a protective or risk factor regarding different social skills ( Filho et al, 2016 ; Muñoz et al, 2017 ; Ansari, 2018 ). In addition, it is important to note that most research has been conducted through questionnaires completed by teachers and parents, and there is a lack of observational research on the prosocial behaviors that children exhibit every day during free-play social interactions with their peers ( Conte et al, 2018 ; Bouchard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aggression increases in preschool years, with a prevalence of 77% [46]. This aggression is usually triggered by a conflict of interests between people, and it tends to be used as an intimidation tool [8].…”
Section: Aggressive Behavior In Childhoodmentioning
confidence: 99%